(untitled) (Bangladesh Journal of Medical Science, 2015)
Anaesthetic management of patients with ventriculoperitoneal shunt (VPS) undergoing laparoscopic surgeries remains controversial for its safety concerns. At present, no standardized protocol exists for managing these patients during perioperative period. The prime concerns are the rise in intracranial pressure (ICP) and shunt dysfunction due to carbon dioxide insufflation. Anaesthetic considerations in these patients should focus primarily on the intrinsic characteristics and functioning of the VP shunt, the insufflation pressures for pneumoperitoneum creation and techniques to monitor the function of shunt. Gasless laparoscopy may be an option by warding off the complications associated with pneumoperitoneum. In our institution, surgeon improvises the laparoscopic technique to create a gasless condition. We discuss the anaesthetic concerns and considerations in this subset of patients for laparoscopy surgeries. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.420-421